Fatsia Japonica-Derived Hierarchical Porous Carbon for Supercapacitors With High Energy Density and Long Cycle Life - Li, Huiling; Cao, Lihua; Wang, Feng; Duan, Gaigai; Xu, Wenhui; Mei, Changtong; Zhang, Guoying; Liu, Kunming; Yang, Meng; Jiang, Shaohua (Frontiers in Chemistry, 2020)
Fatsia Japonica seed, which is mainly composed of glucose, has potential as a porous carbon matrix precursor for supercapacitors that can achieve high-value utilization. Cost-effective hierarchical porous carbon materials (HPC) were prepared from Fatsia Japonica by annealing at high temperature. The pore size and distribution of the HPC can be precisely controlled and adjusted by altering the activation temperature. The HPC obtained at 600°C showed favorable features for electrochemical energy storage, with a surface area of 870.3 m2/g. The HPC for supercapacitors (a three-electrode system) exhibited good specific capacitance of 140 F/g at a current density of 1 A/g and a long cycling life stability (87.5% remained after 10,000 cycles). In addition, the HPC electrode showed an excellent energy density of 23 Wh/Kg. Such hierarchical porous biomass-derived carbon would be a good candidate for application in the electrodes of supercapacitors due to its simple preparation process and the outstanding electrochemical performance.